Analisis Postur Kerja Terhadap Keluhan Gangguan Muskuloskeletal pada Pekerja Pemanen Kelapa Sawit - Rizki Asih Gustara; Susilawati, Susilawati (Yayasan Literasi Sains Indonesia, 2023)
Musculoskeletal diseases (MSDs) are a common complaint because oil palm harvesting is still a manual, labor-intensive and repetitive activity that requires human labour. Due to the non-ergonomic working position, harvesters are prone to musculoskeletal diseases. This study examines the risk factors for musculoskeletal disorders (MSDs) in the agricultural industry using a kind of descriptive analysis and literature review methodology. Five publications were found as a result of a Google Scholar search after a literature search was conducted online at different websites. This research was conducted on 5 publications, all of which were national articles and met the inclusion criteria. To find a solution to a problem, information is evaluated and processed through the steps of organizing, synthesizing, identifying and further analyzing. The findings show that the incidence of musculoskeletal diseases (MSDs) in agricultural workers is influenced by personal factors (age, gender, years of service, medical history, and psychosocial factors), occupational factors (work posture, workload, work duration, repetitive movements and manual materials handling), and environmental factors (work space). Working age is the personal element that is most strongly associated with the occurrence of musculoskeletal diseases (MSDs). Among the workplace and environmental variables that have a substantial correlation with the prevalence of musculoskeletal diseases (MSDs), are work posture and work environment.